ANALISIS TRANSFORMASI MUTU LAYANAN TERHADAP KEPUASAN PASIEN JKN DI RUANGAN RAWAT INAP RSU GRANDMED LUBUK PAKAM - simbolon, maraden (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
One of the most critical aspects of providing patients with quality health care is ensuring their contentment. Direct evidence, dependability, responsiveness, assurance, and empathy are the pillars upon which hospitals must build their top-notch health care services. The study's overarching goal is to draw conclusions about the impact on inpatient happiness in 2024 of the Grandmed Lubuk Pakam Hospital's service quality reform. Analytical surveys are utilized in this study to conduct quantitative research. One thousand nine hundred individuals enrolled in the National Health Insurance (JKN) program were the subjects of this study. A total of ninety-five participants were selected at random for this investigation. Direct evidence (P Value=0.846), responsiveness (P Value=0.03), reliability (P Value=0.03), assurance (P Value=0.011), and empathy (P Value=0.884) were the outcomes of studies that utilized the chi-square statistical test method. Being responsive, reliable, and providing a guarantee are three of the five factors that impact patient satisfaction. In a multiple linear regression analysis, collateral is the primary independent variable. Exp (B) yields 3,250, indicating that the guarantee influences the satisfaction of JKN inpatients at Grandmed Hospital in 2024 by a factor of 3.25. Patients with National Health Insurance who are inpatients at Grandmed Hospital should feel even more secure with the following suggestions, and we can only hope that future studies will take advantage of the ample opportunity to conduct in-depth interviews.